The inflammation spectrum : find your food triggers and reset your system - Cole, Will (Functional medicine expert); Adamson, Eve (Avery, 2019)
"From the international bestselling author of Ketotarian comes a revolutionary new plan to discover the foods your unique body loves, hates, and needs to feel great. In Dr. Will Cole's game-changing new book The Inflammation Spectrum, readers will discover how inflammation is at the core of most common health woes and exists on a continuum: from mild symptoms such as weight gain and fatigue on one end, to hormone imbalance and autoimmune conditions on the other. How you feel is constantly and dynamically being influenced by every meal. Every food you eat is either feeding inflammation or fighting it. Because no one else is you, the foods that work well for someone else may not be right for your body. At heart, The Inflammation Spectrum is about learning to love your body enough to nourish it with delicious, healing foods. Its insightful quizzes and empowering advice will put you on a path toward food freedom and overall healing"--